, a commonly consumed food, affects sirolimus level in a renal transplant recipient: a case report - Melek Kurtaran; Neriman Sila Koc; Melek Seren Aksun; Tolga Yildirim; Şeref Rahmi Yilmaz; Yunus Erdem (SAGE Publishing, 2021)
Sirolimus is an immunosuppressive drug used to prevent graft rejection. Therapeutic drug monitoring is required as with other immunosuppressive drugs. Previous studies have shown the interactions between sirolimus and drugs that affect the activity of cytochrome P450 3A4 and P-glycoprotein. There is an increasing tendency for the use of herbal remedies in many countries. Medicinal herbs are rich sources of natural bioactive compounds that could interact with drugs. Parsley, Petroselinum crispum , is a food, spice, and also a medicinal herb. We report a case of a renal transplant recipient who had a supratherapeutic blood level of sirolimus due to consuming excessive parsley to highlight a possible herb-drug interaction. This is the first case report describing sirolimus-parsley interaction. Herb-drug interactions are especially important for drugs with a narrow therapeutic window. For this reason, healthcare professionals should question all patients, especially transplant patients, about the use of herbs or herbal products and report interactions. Plain Language Summary Parsley, a commonly consumed food, affects the level of an important drug in a renal transplant recipient: A case report Sirolimus is a drug that suppresses the immune response used to prevent organ rejection in people who have had kidney transplants. In order to reach the optimum balance between therapeutic efficacy and adverse effects, sirolimus blood levels should be closely monitored. Previous studies have shown the interactions between sirolimus and drugs that affect the activities of metabolizing enzymes and transporter proteins. Parsley is a food, spice, and also a medicinal herb. Medicinal herbs are rich sources of natural bioactive compounds that could interact with a prescription drug. We report a case of a renal transplant recipient who had a rise in the blood level of sirolimus due to the ingestion of an excessive amount of parsley to highlight possible herb-drug interaction.